2014
DOI: 10.4317/jced.51479
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of holy basil mouthwash as an adjunctive plaque control agent in a four day plaque regrowth model

Abstract: Objectives: Various antibacterial and antiplaque agents are used in chemical plaque control but none are without their shortcomings. Chlorhexidine considered a gold standard, also has an array of side effects. To overcome these, numerous herbal extracts have been tried and tested and one among them is holy basil. The present study evaluated the antibacterial efficacy of holy basil in vitro against some periodontopathogens and its antiplaque effect in vivo. Study Design: Thirty periodontally healthy volunteers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Due to an increased awareness of indigenous medical practices in various parts of the world, the use of "herbal" medicine has engendered interest and facilitated the growth of complementary and alternative therapies in health care promotion. Herbal ingredients have been present in oral care products, more commonly in South Asian countries, for some time [7][8][9]. The most common herbal ingredients to be incorporated into oral care products (e.g., toothpaste and mouth rinse) are sanguinarine, propolis, Azadirachta indica (neem), charcoal, clove, and miswak [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to an increased awareness of indigenous medical practices in various parts of the world, the use of "herbal" medicine has engendered interest and facilitated the growth of complementary and alternative therapies in health care promotion. Herbal ingredients have been present in oral care products, more commonly in South Asian countries, for some time [7][8][9]. The most common herbal ingredients to be incorporated into oral care products (e.g., toothpaste and mouth rinse) are sanguinarine, propolis, Azadirachta indica (neem), charcoal, clove, and miswak [10].…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al [ 27 ] in their study compared the effectiveness of Tulsi extract with gold standard chlorhexidine on PI and gingival inflammation concluded that Tulsi extract was equally effective as 0.12% chlorhexidine mouthwash. Hosamane et al [ 28 ] in their study found that Tulsi extract was effective in inhibiting growth of P. intermedia and F. nucleatum in vitro , they used Tulsi extract as mouth wash and reported statistically significant reduction in plaque score in groups where Tulsi was used as mouth wash in comparison to sterile water and showed similar reduction in plaque scores when compared to 0.2% chlorhexidine mouthwash indicating that Tulsi is as effective antiplaque agent as chlorhexidine mouthwash which is known for its antiplaque activity. These studies compared and concluded that Tulsi as mouthwash is as effective as chlorhexidine mouthwash; thus, giving scope for the use of Tulsi as LDD agent.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Hosamane et al . in an in vitro model,[18] a significant reduction with respect to PI in a 4 days plaque regrowth model in the O . sanctum group was reported.…”
Section: Discussionmentioning
confidence: 99%